ANALISIS PENDAPATAN DAN BIAYA POKOK USAHATANI KEDELAI DI KECAMATAN AMBARAWA KABUPATEN PRINGSEWU - Putri Alamanda; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
The objectives of this research were to analyze the revenue and the standard cost of the soybean farming in Ambarawa District, Pringsewu Regency. Respondents were the soybean farmers chosen by using simple random sampling method. The data were the soybean farming in the Dry Season (DS) 2017. The data were analyzed by using the financial analysis. Based on the reseach, the average soybean productivity was 1.31 ton/ha. The average net revenue over the cash costs and over the total cost respectively were IDR 6.76 million/ha and IDR 1.45 million/ha. The average standard cost for producing soybean was IDR 7,061/kg and its 95% confidence interval was IDR 5,559/kg - IDR 8,562/kg.Key words: revenue, soybean, standard cost.